Edge Colouring of Neutrosophic Graphs and Its Application in Detection of Phishing Website - Rupkumar Mahapatra; Sovan Samanta; Madhumangal Pal (Discrete Dynamics in Nature and Society)
Graph colouring enjoys many practical as well as theoretical uses. Graph colouring is still a very active subject of research. This article introduces a new concept of the chromatic number of the neutrosophic graph (NG). There is a discussion of the difference between the fuzzy colouring of the fuzzy graph (FG) and the NG. Finally, a real-life application for detecting phishing websites has been demonstrated by NG colouring.